Pengaruh Ekstrak Rimpang Kunyit (Curcuma longa L.) Terhadap Aktivitas Motorik Tikus Putih Pada Model Parkinson - Farisa, Siti; Ikhsan, Maulana; Novalia, Vera (Universitas Mohammad Husni Thamrin, 2025)
Parkinson's disease is a neurodegenerative disease characterized by movement disorders such as bradykinesia, rigidity, and tremor that can affect body balance, due to decreased dopamine levels that can be triggered by oxidative stress. Turmeric (Curcuma longa) contains curcumin which has antioxidant and neuroprotective properties, making it possible to prevent neurodegenerative disorders due to oxidative stress. Turmeric rhizome has a chemical content that is a yellow color substance called curcuminoids. This study aims to determine the effect of administering turmeric rhizome extract (Curcuma longa L.) on the motor activity of white rats (Rattus norvegicus) in the Parkinson's model. This study uses a laboratory test method using a pretest-posttest only control group design that uses white rat (Rattus novergicus) male wistar strain as the object of research. This study used 6 white rats carried out with 4 sample groups, with a total of 24 white rats (Rattus norvegicus) male wistar strains. This research has obtained ethical approval from the Ethics Committee of Health Research, Faculty of Medicine, Malikussaleh University, with letter number: 09/KEPK/FKUNIMAL-RSUCM/2023. The results showed that turmeric rhizome extract (Curcuma longa L.) at a dose of 600mg / kgBB had an effect on the motor activity of white rats (Rattus norvegicus) in the Parkinson's model, turmeric rhizome extract (Curcuma longa L.) at a dose of 400mg kgBB had an effect on the motor activity of white rats (Rattus norvegicus) in the Parkinson's model. There is no significant difference in the effect of turmeric rhizome extract between the dose groups of 400 mg/KgBB and 600 mg/KgBB on increasing the motor activity of white rats (Rattus norvegicus) in the Parkinson's model Keywords: Antioxidat, Haloperidol, Parkinson's Disease, Turmeric Rhizome, White Rat